Quality of Work Life, Health Status and Associated Factors Among Workers of Ready-Made Garment Factory in Dhaka City (Journal of Preventive and Social Medicine, 2025)
Background: The Ready-Made Garment (RMG) sector is the largest contributor to Bangladesh’s economy, employing approximately 3.6 million workers, 80% of whom are women. Despite its economic significance, poor working conditions negatively impact workers' health and quality of work life (QWL). This study aims to assess the quality of work life (QWL) among garment workers in Dhaka and effects of related factors and health problems influencing it. Methods: A cross-sectional study was conducted among 110 garment workers from two factories in Dhaka between March and June 2021. Data were collected using a semi-structured questionnaire, including socio-demographic details, work-related factors, QWL measured by the Inventory for Measuring Quality of Work Life (QWL), and health status assessed using the Inventory of Subjective Health (ISH). Results: The mean age of participants was 23.25 ± 5.29 years, with 70.0% aged ≤25 years and 69.1% being female. About 39.1% had secondary or higher education, and 61.8% were married. Most (64.5%) had a monthly family income of ≤13,500 BDT. Over half (53.6%) had 1–3 years of experience, and 60.9% worked in the sewing section. More than half (50.9%) reported low or unsatisfied QWL. Significant factors associated with high QWL included younger age (p=0.000), secondary or higher education (p=0.000), higher income (p=0.002), and working in the sewing section (p=0.000). Common health issues included fatigue (97.3%), hand tremors (95.5%), musculoskeletal pain (73.6%), fever (72.7%), cough (57.3%), and eye strain (39.1%). Logistic regression showed younger workers (≤25 years) were 5.95 times more likely to report high QWL (p